USING THREE STEP-INTERVIEW TO IMPROVE STUDENT’S SPEAKING ABILITY - Aristy, Ismi; Hadiansyah, Rega; Apsari, Yanuarti (IKIP Siliwangi, 2019)
Speaking can be defined as an activity to share or discuss information that helped people to communicate with each other. To improve the students’ speaking learning interest, the teacher needs to recognize how to teach speaking effectively, and what instructional materials are the most appropriate for their students. The aims of the research are to find out whether or not teaching speaking using three – Step interview technique in improving students’speaking ability and to find out the teaching and learning situation when three – Step interview technique implemented in the speaking class.This research is Classroom Action Research. The data was collected through observation, interview and test. The respondents of this research were the seventh grade students of SMP Putra Juang Cianjur.This research revealed that the pre-test data the average was 45,86. After implementing the three-step interview technique in every cycle, the students’ speaking score was getting better. It can be seen from the result of students' average score Cycle 1 was 51,60 and Cycle 2 was 60,26 It can be concluded that the three-step interview technique can improve students’ speaking interest and three step interview technique can improve speaking classroom into a better situation. Keywords: three step interview, speaking interest, CAR.